Lead Markets as A Source Of Innovations in South-East Asian Countries - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
This paper explores whether market conditions in South East Asia are able to induce innovations that can be successfully commercialised globally. The propensity ofa national market to adopt innovations before other countries can be characterised as a lead market. Hitherto the competitiveness of South East Asian countries .has been considered to rest in natural resources and low factor costs. Western industrialised countries as well as Japan, on the other hand, are suggested to gain international conzpetitiveness in industries through domestic demand advantage. A demand advantage stems from demanding users and demand for superior goods. This paper argues that developing countries too can successfully foster competitive new industries based on demand advantage. Based on a system of the five main factors that facilitate the lead market role of a country, examples of potential lead markets in South East Asia are given in port technology, health services and hair and skin care. Multinational firms are advised to focus new innovation development (marketing, R&D) on those countries, which have a lead market advantage in order to generate global innovations.